Role of Organic Matter Present in the Water Column on Turbidity Flows - Shaheen Akhtar Wahab; Waqas Ali; Claire Chassagne; Rudy Helmons (Journal of Marine Science and Engineering)
Turbidity flows are known to be affected by the density difference between sediment plumes and the surrounding water. However, besides density, other factors could lead to changes in flow propagation. Such a factor is the presence of suspended organic matter. Recently, it was found that flocculation does occur within plumes upon release of a sediment/organic matter mixture in a lock exchange flume. In the present study, mineral sediment (illite clay) was released into the outflow compartment containing water and synthetic organic matter (polyacrylamide flocculant). Even though the density of water was barely affected by the presence of flocculant, flow head velocity was observed to be larger in the presence of flocculant than without. Samples taken at different positions in the flume indicated that flocs were created during the small current propagation time (about 30–60 s) and that their sizes were larger with higher flocculant dosage. The size of flocs depended on their positions in the flow: flocs sampled in the body part of the flow were larger than the ones sampled at the bottom. All these properties are discussed as a function of sediment–flocculant interactions.